It's kind of a funny story - Vizzini, Ned, 1981- (New York : Miramax Books/Hyperion Books For Children, 2006)
A humorous account of a New York City teenager's battle with depression and his time spent in a psychiatric hospital.
700
Accelerated Reader AR
A Junior Library Guild selection.
Keywords: Depression, Mental -- Juvenile fiction; Mental illness -- Juvenile fiction; Psychiatric hospitals -- Juvenile fiction; New York (N.Y.) -- Juvenile fiction